Kaset Rojananil [Thailand, Royal Thai Armed Forces] - Rojananil, Kaset (Institutional Knowledge at Singapore Management University, 2015)
Kaset Rojananil was the Supreme Commander of the Royal Thai Armed Forces during the Black May riots of 1992 and was involved in the 1991 coup to overthrow the government of Chatichai Choonhavan. He gives DNA his take on those events as well as what it takes to be a leader in the military.